Bantuan Korea Selatan untuk Penanganan COVID-19 di Ethiopia melalui ABC Program Tahun 2020–2021 - Safitri, Helma; Aisyah, Aisyah (Interdependence Journal of International Studies, 2023)
South Korea is helping the response to COVID-19 in Ethiopia through the ABC Program in 2020–2021. Assistance through this program is included in ODA Korea: Building TRUST. This study aims to analyze the reasons why South Korea provides assistance in handling COVID-19 in Ethiopia with this program by using decision-making theory as an analytical tool. Based on this research, the reasons for South Korea can be seen from internal and external setting factors. Setting internal factors include, South Korea is trying to increase national branding during the COVID-19 pandemic and South Korea's success in handling the COVID-19 pandemic domestically provides a comparative advantage in the form of resources to help handle COVID-19 externally. Meanwhile, the external setting factor is the openness of the Ethiopian government to international assistance due to the government's low capacity in dealing with COVID-19, the potential for increased vulnerability of the Ethiopian community due to COVID-19, as well as the interests of the two countries to improve bilateral relations that have been built since the Korean War in 1950.